Analysis Of The Performance Of Solar Power Plants (Plts) On The Electrical Energy Needs Of Mosques - hafit, ilhan; Wibowo, Pristisal; Siagian, Parlin (Universitas Nurul Jadid, 2025)
The need for electrical energy continues to increase, including in public facilities such as mosques. Solar energy is an environmentally friendly and sustainable solution because it is a source of renewable energy. This study aims to analyze the feasibility of implementing a rooftop Solar Power Plant (PLTS) system at Al-Hakim Mosque, Mabar Hilir Village, which has high sunlight intensity and minimal vegetation obstructions. The methods used include direct observation and interviews. The data collected included location identification, energy needs, and calculations of the solar power system. The results show that the mosque requires a daily power of 7,860 Wh, which can be met with 16 100 Wp solar panels and 9 12V 100Ah LiFePO₄ batteries. The research concluded that the location of the Al-Hakim Mosque is suitable for the implementation of the solar power system, while supporting the renewable energy transition and government policies towards energy sustainability in Indonesia